Backend Design and Development of Thesis Management and Scheduling Application Using Rule-Based Algorithm in Physics Department UPN “Veteran” Jatim - Eka Dyar Wahyuni; Reisa Permatasari; Andhika Rizky Aulia (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Thesis administration in higher education can be complex, especially in programs like Physics that previously lacked a structured system for managing thesis activities and seminar schedules. To address this, a backend system was developed to streamline these processes using a rule-based algorithm. The system supports multiple user roles—including students, lecturers, thesis coordinators, program coordinators, and administrators—by providing web-accessible API services. Key features include user authentication, pre-proposal submission, advisor assignment, seminar scheduling (proposal and final), oral examination coordination, and graduation document submission. The development followed the Scrum methodology over six sprint cycles, with each cycle aimed at improving functionality and ensuring system stability. To ensure the system met all functional requirements, black-box testing was conducted. The final version was deployed on a cloud hosting platform using Cloud Run, enabling public access to its API services. This solution is intended to enhance efficiency, reduce administrative workload, and provide a centralized, accessible platform for all stakeholders involved in the thesis process.